A Systematic Review of Lower Extremity Return to Sport. Issue 4 (November 2022) - Smiley, Traci; Dallman, Johnathan; Aldag, Levi; Mok, Anthony C.; Tarakemeh, Armin; Burki, Megan; Martin, Kyle; Vopat, Bryan G.
Category: Sports; Ankle; Other Introduction/Purpose: A uniform criterion has not been established for return to sport (RTS) testing which is complicated by the lack of a standardized definition of the term RTS. Most commonly, RTS is defined as playing in at least one game of the athletes' respective sport, or the first game played after treatment.1 However, the timeline from the injury and/or treatment date to RTS varies amongst each physician or institution. Regarding the ankle, there is an enormous paucity of functional testing research. Therefore, the purpose of this project is to review current literature for joint-specific and global lower extremity testing to determine the most valid functional test that can be utilized to prevent re-injury as athletes RTS. Methods: A systematic search of PubMed, PubMed Central, Cochrane Library, OVID, and Embase databases was conducted to identify clinical studies that included evaluation of a return to sport test or functional test (single test or test battery) for the lower extremities. Both operative and non-operative treatments included in this review. Only studies that had patients between the ages of 14 years old and 40 years old were included. Specfici rehab protocik or treatment plan, non-English publications, non- human or cadaver studies, and studies that did not evaluate return to sport test or function test were excluded. Results: Of 8, 705 studies, 65 (0.7%) studies published through October of 2021 met inclusion criteria and were analyzed. 52 out of 65 (80%) articles discussed RTS for the knee. Furthermore, 50 out of the 52 (96%) specifically analzyed RTS following ACLR. With this said, we did not abandon ankle and hip RTS cases. Discussed herein, are numerous RTS tests including the most common, isokinetic dynamometry testing which is seen in 38 out of the 52 (73%) of the knee RTS cases. Unfortunately, only 4 out of 65 (6.2%) studies analyzed RTS for the hip and 1 out of the 65 (1.5%) barely touched on the ankle. The remaining studies analyzed healthy participants only. Conclusion: More research is clearly required to identify the most valid functional test batteries for joint-specific RTS lower extremity testing. Even with the enormous amount of literature that exists regarding ACL injuries and testing there is no standardized criterion for RTS clearance. As seen in this review, the research available for the hip and ankle is substantially scarcer in regards functional testing. We hope that the suggested test batteries from this review can serve as a framework for future research and validation for joint-specific RTS functional testing.